APPLICATION OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS AND DEVELOPMENT OF ATTENTION - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
Based on the various forms, numerous teaching methods have emerged that are applied and practiced in practice and continue this process. The way the path, the way a particular ACT of learning is designed, is a form of self-study designed to achieve this goal. Here are some of the paths that can be taken as measures for the required activity and the path chosen according to the intended purpose.